Cost-utility of afatinib and gefitinib as first-line treatment for EGFR-mutated advanced non-small-cell lung cancer. (15th October 2018) - Wang, Hao; Zeng, Chenxin; Li, Xin; Wang, Youjie; Li, Xinyi; Ge, Weihong
Aim: To evaluate the cost-utility of gefitinib and afatinib as first-line EGFR -mutated non-small-cell lung cancer treatments from the Chinese healthcare system perspective.Materials & methods: A Markov model was established, state transition probabilities were extracted from the LUX-Lung7 trial and utility values were from previous studies. The cost was extracted from local charge or relevant literature. Incremental cost–effectiveness ratio was calculated for intention-to-treat, EGFR exon 19 deletion (del19) and exon Leu858Arg (21L858R, L858R) muation subgroups. Results: For the entire population, the afatinib regimen afforded additional 0.29 quality-adjusted life years (QALYs). Incremental cost–effectiveness ratios were US9820.41/QALY, US18, 529.65/QALY and US1585.51/QALY for intention-to-treat, L858R and del19, respectively.Conclusion: First-line afatinib was more cost–effective than gefitinib for EFGR-mutated advanced non-small-cell lung cancer in China.